Synthesis and characterization of a novel fluorinated bismaleimide via a nucleophilic addition–elimination reaction and its polymeric networks1. Issue 92 (8th October 2015) - Wu, Jingbo; Xi, Yang; McCandless, Gregory T.; Kulikov, Oleg V.; Menon, Remya; Novak, Bruce M.
<x xml:space="preserve">Abstract</x> A novel fluorinated bismaleimide, OFCP-BMI, was designed and readily synthesized via the nucleophilic addition–elimination reaction of octafluorocyclopentene with maleimide-functionalized phenol.